Efforts to Improve Non-Manipulative Basic Movement Skills through Collaborative Gymnastics for Students - Nurul Shahnaz Umairha Sianipar; Khairul Usman; Ika Endah Puspita Sari; Alan Alfiansyah Putra Karo Karo (Journal Of Sport Education (JOPE), 2025)
Non-manipulative basic motor skills are fundamental abilities that need to be developed from an early age as a basis for mastering further motor skills. However, initial observations show that the non-manipulative basic motor skills of first-grade students at MIS Al-Barkah Percut Sei Tuan are still in the low category. This study aims to improve non-manipulative basic motor skills through the application of Medan collaborative gymnastics. The research method used was classroom action research (CAR) conducted in two cycles, with 20 first-grade students at MIS Al-Barkah Percut Sei Tuan as the research subjects. Each cycle consisted of the planning, implementation, observation, and reflection stages. Data collection techniques were carried out through observation of students' basic non-manipulative motor skills, while data analysis was conducted using quantitative descriptive methods. The results showed an increase in students' non-manipulative basic motor skills from cycle I to cycle II after the implementation of Medan collaborative gymnastics. This improvement was seen in the aspects of balance, flexibility, and coordination of students' movements. Thus, the implementation of Medan collaborative gymnastics proved to be effective in improving the non-manipulative basic motor skills of first-grade students at MIS Al-Barkah Percut Sei Tuan.